Sublytic Membrane-Attack-Complex (MAC) Activation Alters Regulated Rather than Constitutive Vascular Endothelial Growth Factor (VEGF) Secretion in Retinal Pigment Epithelium Monolayers - Kunchithapautham, Kannan (American Society for Biochemistry and Molecular Biology, 2011)
Uncontrolled activation of the alternative complement pathway and secretion of vascular endothelial growth factor (VEGF) are thought to be associated with age-related macular degeneration (AMD). Previously, we have shown that in RPE monolayers, oxidative-stress reduced complement inhibition on the cell surface. The resulting increased level of sublytic complement activation resulted in VEGF release, which disrupted the barrier facility of these cells as determined by transepithelial resistance (TER) measurements. Induced rather than basal VEGF release in RPE is thought to be controlled by different mechanisms, including voltage-dependent calcium channel (VDCC) activation and mitogen-activated protein kinases. Here we examined the potential intracellular links between sublytic complement activation and VEGF release in RPE cells challenged with H(2)O(2) and complement-sufficient normal human serum (NHS). Disruption of barrier function by H(2)O(2) + NHS rapidly increased Ras expression and Erk and Src phosphorylation, but had no effect on P38 phosphorylation. Either treatment alone had little effect. TER reduction could be attenuated by inhibiting Ras, Erk and Src activation, or blocking VDCC or VEGF-R2 activation, but not by inhibiting P38. Combinatorial analysis of inhibitor effects demonstrated that sublytic complement activation triggers VEGF secretion via two pathways, Src and Ras-Erk, with the latter being amplified by VEGF-R2 activation, but has no effect on constitutive VEGF secretion mediated via P38. Finally, effects on TER were directly correlated with release of VEGF; and sublytic MAC activation decreased levels of zfp36, a negative modulator of VEGF transcription, resulting in increased VEGF expression. Taken together, identifying how sublytic MAC induces VEGF expression and secretion might offer opportunities to selectively inhibit pathological VEGF release only.